Macromedia Flash 8 Learning Media to Increase Learning Interest in Theme 2 Students Always Save Energy Class IV SD Negeri 016555 Asahan - Wulandari, Vita; Landong, Ahmad (Widyagogik, 2022)
This study aims to: (1) develop media using Macromedia Flash 8 applications in elementary thematic learning, (2) determine the feasibility of developing Canva applications in elementary thematic learning. This research is a type of Research and Development (RD) research with the ADDIE model which includes five steps, including: analysis, Design, Development, Implementation, Evaluation . The subjects in this study were media expert validators, material experts, education practitioners, namely fourth grade teachers and fourth grade elementary school students. The research instruments used in data collection were questionnaires, observations, and documentation. The results of this study indicate that the Macromedia Flash 8 Application learning media in the Thematic Learning of the Always Save Energy Theme for Grade IV Elementary School is "Very Eligible" with details of the percentage of eligibility given by media experts in Sub Theme 1 of 86.6% with the category of "Very Eligible", Sub Theme media 2 of 83.3% in the "Very Eligible" category, Sub Theme media 3 by 86.6% in the "Very Eligible" category. Material experts on media Sub Theme 1 are 94% in the "Very Eligible" category, Sub Theme 2 is 94% in the "Very Eligible" category, Sub Theme 3 is 92% in the "Very Eligible" category. For education practitioners in media Sub Theme 1, 94% in the "Very Eligible" category, 94% in Sub Theme 2 in the "Very Eligible" category, 94% in Sub Theme 3 in the "Very Eligible" category, Individual trials of 95.2% with the "Very Eligible" category and small group trials of 93.7% with the "Very Eligible" category. Therefore, it can be concluded that the Macromedia Flash 8 Application learning media in the thematic learning of the Always Save Energy for grade IV SD Negeri 016555 Asahan is "very feasible" to be used by students during the learning process.